Life on Mars - Agee, Jon (New York : Dial Books for Young Readers, 2017)
A young astronaut is trying to find life on Mars, but he's made a very big oversight.
School Library Journal starred, December 2016
Horn Book Starred, January 2017
Kirkus Starred, November 2016
Booklist, January 2017
Bulletin (Center for Children's books), January 2017
Publishers Weekly Annex, January 2017
Keywords: Astronauts -- Fiction; Life on other planets -- Fiction; Mars (Planet) -- Fiction; Astronauts -- Fiction; Life on other planets -- Fiction; Mars (Planet) -- Fiction